2023
DOI: 10.1038/s41598-023-28263-2
|View full text |Cite
|
Sign up to set email alerts
|

Owner-rated hyperactivity/impulsivity is associated with sleep efficiency in family dogs: a non-invasive EEG study

Abstract: Subjective sleep disturbances are reported by humans with attention-deficit/hyperactivity disorder (ADHD). However, no consistent objective findings related to sleep disturbances led to the removal of sleep problems from ADHD diagnostic criteria. Dogs have been used as a model for human ADHD with questionnaires validated for this purpose. Also, their sleep physiology can be measured by non-invasive methods similarly to humans. In the current study, we recorded spontaneous sleep EEG in family dogs during a labo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Particularly, cognitive dysfunction is commonly observed in aged dogs, and this could be related to sleep and activity similar to humans [ 7 , 10 , 18 ]. Dogs with hyperactivity/impulsivity showed less sleep quality and quantity [ 5 ]. In addition, human sleep can be influenced by dogs and cats [ 8 , 15 ], and this method can apply to the research for understanding the relationship between pets and owners living together in a house.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, cognitive dysfunction is commonly observed in aged dogs, and this could be related to sleep and activity similar to humans [ 7 , 10 , 18 ]. Dogs with hyperactivity/impulsivity showed less sleep quality and quantity [ 5 ]. In addition, human sleep can be influenced by dogs and cats [ 8 , 15 ], and this method can apply to the research for understanding the relationship between pets and owners living together in a house.…”
Section: Discussionmentioning
confidence: 99%
“…On a different association with sleep quality, Carreiro et al [19] investigated the relation between sleep activity and owner-rated hyperactivity and found that dogs rated as more hyperactive and impulsive demonstrated less total sleep time, a reduced percentage of REM sleep, and lower spindle density compared to dogs rated as less hyperactive and impulsive. Moreover, owner-rated hyperactivity and impulsivity were associated with increased wakefulness after sleep onset and greater sleep fragmentation.…”
Section: Sleep Eeg In Dogsmentioning
confidence: 99%
“…Our review ends by underscoring the advances and advantages of EEG-based canine cognitive neuroscience and the potential for accessible canine neuroimaging to inform both fundamental sciences as well as practical applications for cognitive neuroscience, working dogs, and human-canine interactions.Keywords canine science • cognitive neuroscience • EEG Berns et al pioneered the use of fMRI in awake, non-restrained dogs in 2012 [8], and in the following year, Kujala and colleagues were the first to successfully deploy non-invasive EEG with non-sedated dogs [61]. Further developments Non-invasive canine electroencephalography (EEG): a systematic review PREPRINT included the investigation of a range of cognitive processes and their neural underpinnings such as executive functioning [24], visual [25,61], auditory [5,17], and olfactory [50] processing, social cognition [23], learning [88] and sleep [19,56]. While the field of canine fMRI has received increasing scientific attention, non-invasive canine EEG has eluded similar treatment.…”
mentioning
confidence: 99%
“…Sleep data is relatively easier to collect, as motion is limited, and large quantities of data can be recorded quickly. From the literature, a canine BCI would be able to achieve the following capabilities - Previous studies have found that certain power spectral density bands, specifically beta and delta, correlated with learning rates [72], and that features of spindles, such as the frequency, density, and amplitude, correlated with cognitive traits such as learning gain [73,74], memory consolidation [73], cognitive ageing [75], and owner rated hyperactivity [76]. ( 4) Make predictions on human-canine relationship dynamics based on sleep features.…”
Section: Insight and Predictions From Sleepmentioning
confidence: 99%